Assessing the Precision of Ultrasound in Diagnosing Acute Appendicitis - Khalaf Raieed M Aldosari Zaid Abdullah AlMeshari AlTamimi Faisal Amer Saeed AlShahrani Tarek Obid Alharbi Saeed Ishq Saeed Alqahtani Abdulaziz Ahmed Ibrahim AlHaqwi (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Acute appendicitis is a frequently occurring abdominal ailment that is well-known for its difficult diagnosis. It is critical to get an accurate and timely diagnosis in order to reduce the dangers of postponing surgical surgery. The purpose of this study is to evaluate the diagnostic performance of ultrasonography in Saudi Arabian patients of acute appendicitis in comparison with histological results. It also aims to investigate any possible relationship between the proficiency of the sonographers participating and the accuracy of ultrasound in identifying acute appendicitis.A retrospective analysis was carried out on patients who had ultrasonography examination and who presented to the emergency department with a clinical suspicion of acute appendicitis. Every patient had multiple diagnostic criteria recorded, including wall thickness, compressibility, appendix visibility, free fluid presence, appendix diameter ≥7 mm, and compressibility.The findings showed that only 61 of the 132 patients had an appropriate ultrasonography diagnosis. Of these, 17 were true negatives and 44 were true positives for appendicitis. On the other hand, 2 patients with negative histological findings were mistakenly diagnosed as positive on ultrasonography, and 69 patients with positive histopathological results were given false negative ultrasound diagnosis. Remarkably, there was no discernible correlation found between the sonographers' experience level and ultrasound accuracy.The study's findings highlight the inadequate diagnostic precision of ultrasonography in the identification of instances of acute appendicitis. Moreover, it implies that sonographers' years of expertise had little bearing on how accurately acute appendicitis was diagnosed by ultrasonography.